Young scientists benefit from cross-CGIAR expertize in digital innovation for agriculture - CGIAR (CGIAR System Organization, 2023)
The CGIAR Initiative on Digital Innovation has partnered with Sri Sri University in Cuttack, Odisha to launch an International Certificate Course on Digital Agriculture. The online course is targeted at young scientists and researchers pursuing their bachelor’s degree in either agriculture, environmental sciences or data science.